Deciphering the Energy Transfer Mechanism Across Metal Halide Perovskite-Phthalocyanine Interfaces - Cortés-Villena, Alejandro; Cadranel, Alejandro; Azizi, Kobra; Torres, Tomás; Guldi, Dirk Michael; Pérez-Prieto, Julia; Galian, Raquel E. (Advanced Science, 2025)
Energy transfer processes in nanohybrids are at the focal point of conceptualizing, designing, and realizing novel energy-harvesting systems featuring nanocrystals that absorb photons and transfer their energy unidirectionally to surface-immobilized functional dyes. Importantly, the functionality of these dyes defines the ultimate application. Herein, CsPbBr3 perovskite nanocrystals (NCs) are interfaced with zinc phthalocyanine (ZnPc) dyes featuring carboxylic acid. The functionality is the photosensitization of singlet oxygen. The CsPbBr3@ZnPc nanohybrid is to the best of our knowledge the first example, in which an unusual Dexter-type singlet energy transfer between metal halide perovskite nanocrystals and phthalocyanine dyes enables singlet oxygen generation as a proof-of-concept application. A detailed temporal picture of the singlet energy transfer mechanism is made possible by combining key time-resolved spectroscopic techniques, that are, femtosecond, nanosecond, and microsecond transient absorption spectroscopy as well as time-correlated single photon counting, and target analyses. In fact, three excitonic components in the NCs govern a concerted Dexter-type energy transfer. The work illustrates the potential of CsPbBr3@ZnPc as a singlet photosensitizer of ZnPc to produce singlet oxygen (1O2) almost quantitatively while photoexciting CsPbBr3.
CRIS-Team Scopus Importer:2025-01-31
Keywords: perovskite nanocrystals; perovskite-phthalocyanine nanohybrids; singlet energy transfers; time-resolved photoluminescence; transient absorption spectroscopy